An overview of dominant research approaches to measure Intercultural Communication Competence (ICC) - Nadeem, Muhammad Umar; Mohammed, Rosli; Dalib, Syarizan (2018)
The aim of this paper is to discuss the several dominant research approaches incorporated by the intercultural researchers of the past. These approaches are elaborated into two different manners. Firstly, an overview of the six prominent theoretical approaches is discussed briefly along with the lacking and culture-specific elements in the approaches are witnessed. Secondly, culture general approaches are considered with their importance in the research practice regarding their culture general nature. Following with the remarkable contributions towards the current body of knowledge by Lily A. Arasaratnam in intercultural communication competence (ICC). In addition, it is also pointed out that how she developed such culture general models of ICC with a thorough discussion on the series of her culture general models. It is noticed from the literature on intercultural competence that previous approaches and culture general model are mostly addressed in the Western context. Even though context does matter a lot in the intercultural research. Therefore, it is suggested to explore these approaches and culture general models of multiple cultural perspectives, especially in Non-Western contexts to validate their culture-general nature.